Organization of Data Analytics in a Company - Felix ESPINOZA; Milos MARYSKA; Petr DOUCEK (Communications of International Proceedings, 2024)
The paper explores the complex decision-making process involved in determining the organizational structure for data analytics within a company. Before selecting whether a centralized, decentralized, or federated model is most appropriate, it's crucial to accurately define the scope of data analytics within the enterprise and specify the roles it will fulfill. Each variation of organizational models for data analytics carries its own unique social implications. For instance, centralization provides managers with exclusive control over essential information, whereas decentralization promotes data sharing and nurtures a stronger sense of belonging among employees. It's important to ensure alignment between the chosen organizational model and the predefined organizational units/roles, including their associated rights and responsibilities. This paper offers a thorough examination of the responsibilities of four distinct units: BI & Data Governance, Central Analytics, and Advanced Analytics, proposed for centralization, alongside the Business Analytics unit, recommended for decentralization.
Keywords: centralization; decentralization; data analytics; governance; organizational model